The Gravestone of Metrodoros from the Excavations of the Southern Suburb of Chersonesos Taurica - Trofimova, Anna; Pavlichenko, Natalia (Hyperboreus, 2022)
The paper is devoted to the publication of a newly found gravestone from the excavations of the Southern Suburb of Chersonesos Taurica. The funerary stele belongs to a known Chersonesean type: the deceased is depicted within an aedicule niche, frontally, completely wrapped in a long himation. The youth’s head displays individual features. The style of the work echoes peculiarities of the Roman portraiture of Trajan’s reign. The composition of the stele, the character of the drapery and the hairstyle make it possible to date the relief to ca. 125–150 AD. The gravestone was produced locally, in Chersonesos, with the portrait most probably being added to an already half-finished workpiece. The epigraph on the stone has survived in its entirety (the type is datable to ca. 125–175 AD), and a reading of it not only provides information about the dead youngster, Μητρόδωρος Ἀπολλωνίδου, but also sheds light on the technology used to make lapidary inscriptions in the Northern Black Sea region. Directly under the epitaph of Metrodoros, three lines of another inscription are discernible, carved in thin and rather shallow lines. Their text and the spacing of the words in the lines are absolutely identical to the last three lines of the main inscription; some letters of this “lower” inscription are discernible also above. It may be suggested that this is a so-called ordinatio – i.e. the primary layout of the plate intended for the grave stele.